Mardatilah Values and Islamic Ethical Governance: A Conceptual Framework for Measuring Civil Servant Work Integrity in Muslim-Majority Public Sectors - Endang Sarwiningsih; Emiliana Pudjiarti (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This study develops and empirically tests the Mardatilah Curiosity Motivation model as an Islamic value-based governance framework for enhancing sustainable performance among civil servants in Muslim-majority public sectors. Mardatilah, derived from Arabic al-marḍāh (المرضاة) meaning